The potential role of isothermal calorimetry in studies of the stability of fresh-cut fruits - Rocculi, Pietro (2012)
Attention is drawn to the feasibility of using high sensitivity isothermal heat conduction calorimetry to study metabolic responses of differently processed and stored fresh-cut fruit. The heat production of endogenous (tissue metabolism during 12 h of analysis at 10 °C for kiwifruit and strawberry) and exogenous (microbial growth during 18 d of analysis at 10 °C for cantaloupe) biological processes was investigated. Osmotic dehydration of fresh kiwifruit in sucrose solution (61.5 g/L) at different treatment times (30, 60 and 180 min), resulted in metabolic heat production decrease, confirming the progressive cell death induced by osmotic dehydration. Analysis on strawberry slices under two atmospheric conditions (air and innovative modified atmosphere) seemed to confirm the inhibitory effect of N2O on metabolic activity. Cantaloupe samples immersed in three different syrups (SS: sucrose syrup (20 °Brix); SS1: SS + 0.5 g/L ascorbic acid + 0.5 g/L citric acid; SS2: SS1 + 0.1 g/L potassium sorbate) showed a stability increase when additives with antimicrobial properties were included. Our findings confirm that isothermal calorimetry provides a versatile and high sensitive tool for conducting fundamental metabolic studies on the effect of different processing operations on the quality and shelf life of fresh-cut fruit and vegetables.